Evaluation of the isoniazid preventive therapy care cascade among HIV-positive female sex workers in Mombasa, Kenya - LaCourse, Sylvia M. (J Acquir Immune Defic Syndr, 2017)
BACKGROUND: Kenyan female sex workers (FSWs) have a high HIV prevalence, increasing their tuberculosis (TB) risk. Despite recommendations that HIV-positive individuals be offered isoniazid preventive therapy (IPT), uptake has been limited. METHODS: In this longitudinal cohort of HIV-positive FSWs, we retrospectively characterized the IPT care cascade between March 2000–January 2010, including reasons for cascade loss or appropriate exit. Cascade success required completion of 6 months of IPT. Baseline characteristics were assessed as potential correlates of cascade losses using multivariable logistic regression. RESULTS: Among 642 HIV-positive FSWs eligible for IPT evaluation, median age was 31 years (IQR 26–35) with median CD4 lymphocyte count of 409 (IQR 292–604) cells/mm(3). There were 249 (39%) women who successfully completed 6 months of IPT, 157 (24%) appropriately exited the cascade, and 236 (37%) were cascade losses. Most cascade losses occurred at symptom screen (38%, 90/236), CXR evaluation (28%, 66/236), or during IPT treatment (30%, 71/236). Twenty-nine women were diagnosed with TB, including one after IPT initiation. Most women initiating IPT completed the course (71%, 249/351); <5% had medication intolerance. Younger women (<25 and 25–35 vs. >35 years; adjusted odds ratio [AOR] 2.65, 95% confidence interval [CI] 1.46–4.80 and AOR 1.78, 95% CI 1.13–2.80, respectively), and those evaluated for IPT after antiretroviral availability in 2004 (AOR 1.92, 95%CI 1.31–2.81), were more likely to be cascade losses. CONCLUSIONS: Implementation of IPT among HIV-positive FSWs in Kenya is feasible. However, significant losses along the IPT care cascade underscore the need for strategies improving retention in care.